2020
DOI: 10.1021/acssuschemeng.0c00852
|View full text |Cite
|
Sign up to set email alerts
|

Metallophthalocyanine-Based Polymer-Derived Co2P Nanoparticles Anchoring on Doped Graphene as High-Efficient Trifunctional Electrocatalyst for Zn-Air Batteries and Water Splitting

Abstract: Covalent organic polymers (COPs) provide an interesting platform for constructing the low-cost and highly efficient multifunctional electrocatalysts in view of their tailorable structures and properties. Herein, Co-phthalocyanine-based COPs (CoPc-COPs) are constructed using cobalt tetraaminophthalocyanine (CoPc­(NH2)4) as the organic building unit and phosphonitrilic chloride trimer (Cl6N3P3) as the linker group, which serve as the self-carrier enriched with Co, P, N, and C to derive Co2P nanoparticles anchore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(27 citation statements)
references
References 44 publications
0
26
1
Order By: Relevance
“…Besides, the electrocatalytic HER/OER/ORR activity of Fe-Co 2 P@Fe-N-C catalyst can be comparable to that of most reported transition metal-based trifunctional electrocatalysts (Figure 3a; Tables S1-S3, Supporting Information), [13,[35][36][37][38][39][40][41][42][43][44][45][46] showing its considerable potential for future electrocatalytic applications. Generally, a good long-term electrochemical stability is also extraordinarily important for electrocatalysis.…”
Section: Electrochemical Her Oer and Orr Performancementioning
confidence: 53%
“…Besides, the electrocatalytic HER/OER/ORR activity of Fe-Co 2 P@Fe-N-C catalyst can be comparable to that of most reported transition metal-based trifunctional electrocatalysts (Figure 3a; Tables S1-S3, Supporting Information), [13,[35][36][37][38][39][40][41][42][43][44][45][46] showing its considerable potential for future electrocatalytic applications. Generally, a good long-term electrochemical stability is also extraordinarily important for electrocatalysis.…”
Section: Electrochemical Her Oer and Orr Performancementioning
confidence: 53%
“…In addition, high-resolution XPS spectra of N, P and Fe are also executed. As exhibited in Figure 2c, N 1s has four separated peaks at binding energy (BE) of 398.2, 400.1, 400.9 and 402.7 eV, which represent for pyridinc-N, pyrrolic-N, graphitic-N and oxidized-N. [19,35] The deconvolution of the highresolution P 2p includes five peaks, among which 129.2 and 130.0 eV can be allocated to P 2p 3/2 and P 2p 1/2 of the PÀ Fe bond (Figure 2d). Compared to elemental P (130.2 eV), the P 2p of 129.2 eV is negatively shifted, suggesting that P carries a partial negative charge (δ À ) in iron phosphide compounds.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…In addition to TMPs, recent advances demonstrate that the synergetic effect between carbon matrix and TMPs plays an important role in enhancing the ORR performance, by improvement of electrical conductivity and prevention of nanoparticles' agglomeration. [19][20][21] Moreover, reports and calculations have revealed that heteroatom-doping in carbon materials introduce vacancy defects, and the heteroatom sites synergized with vacancy defects act as the active sites towards ORR. [22][23][24][25] Therefore, combining TMPs with heteroatom-doped carbon is a promising strategy for producing more active sites in ORR catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…2e) is divided into four peaks, which are associated with carbon atom bonds: C-sp 2 (284.6 eV), C-sp 3 (285.5 eV), C-N (286.9 eV), and C=O/C=N (288.9 eV). In the case of N-species, four types of N-containing groups for Zn-NC and Zn-NGC have been verified, including pyridinic (398.5 eV), pyrrolic (400.2 eV), graphitic (401.1 eV), and oxidized (404.3 eV) nitrogen species [40]. The N 1s spectra of ZnCo-NC and ZnCo-NGC can be well-fitted to four peaks located at 398.5, 399.6, 400.2, and 401.2 eV, which correspond to pyridinic-N, Zn/Co-N x , pyrrolic-N, and graphitic-N, respectively (Fig.…”
Section: Articles Science China Materialsmentioning
confidence: 90%